Evaluating King Stropharia mushroom as an intercrop in asparagus and tomato production; the potential for utilizing mushroom residue as a dietary supplement for poultry - Sipasi, Olalekan Ayodele (My University, 2024)
Stropharia rugosoannulata (L.), the King Stropharia or Wine Cap mushroom, is a wood-loving fungus that grows well on organic mulches. Some vegetables can be successfully grown using organic mulches like woodchips or straw. As a result, farmers may be able to enhance their income by intercropping Stropharia mushrooms with their vegetable crops. However, no study has been identified that assesses this strategy's potential or effect on vegetable yields. Two studies were carried out in the Kansas State University Willow Lake Student Farm, Manhattan, KS to evaluate King Stropharia mushroom as an intercrop in vegetables (Asparagus and Tomato) production, as well as a review paper on the potential of utilizing Spent Mushroom Substrate SMS as a dietary supplement in poultry production. The first study looked at intercropping King Stropharia mushrooms and asparagus by applying woodchips at three depths (4, 8, and 12 in), utilized a randomized complete block design (RCBD) with four replications and included bareground controls. Across both 2022 and 2023 asparagus harvest began earlier with decreasing depths of mulch, and therefore lasted longer. Inoculated plots also produced more marketable spears than uninoculated plots. And, 12 in woodchip mulch significantly inhibited asparagus emergence and is therefore not recommended. Stropharia-asparagus intercrop shows great promise. In fact, in 2023, mushrooms were observed in uninoculated plots demonstrating the gregarious growth of Stropharia in woodchip mulch on asparagus plots. The Second study evaluated King Stropharia mushrooms intercropped with tomato using woodchips, wheat straw, and soy straw (all at 6 in depth). The experiment also utilized a randomized complete block design (RCBD) with four replications and included bareground controls. The tomato study also included a positive mulch control using black plastic. In the fall of 2021, black plastic, inoculated wheat straw, and uninoculated soy straw and woodchip mulch provided earlier harvest than unmulched plots, while the soy treatments and bareground and black plastic controls increased total fruit numbers. In 2022, overall tomato production decreased, resulting in no marketable fruit. These results suggest that a Stropharia-tomato intercrop may not be feasible without additional work. The relative success in asparagus plots supports a need for further research to evaluate other Stropharia-vegetable [or fruit] intercrop candidates and/or strategies to improve compatibility. The third chapter was a review paper on the potential of utilizing spent mushroom substrate as dietary supplement in poultry industry. Mushrooms produced enormous residue especially from the growth substrate that end up in landfill and causing several environmental hazards. Research has shown that for every 1kg of culinary mushrooms produced there are 3.25 – 5 kg of SMS, which is able to as dietary supplement into poultry feed directly or indirectly through being fed to mealworms, that are then utilized as protein source for poultry feed. Even as this is a viable solution, it is worthy of note that the inclusion ratio of SMS in poultry and mealworm feed needs to be more studied.
Keywords: Tomato; Mushroom; Asparagus; Intercrop; Poultry feed